Uso de redes sociales en internet, influencia en los hábitos de sueño y su relación con rendimiento académico en adolescentes del Colegio Vilcabamba - Ortega Vicente, Jairo Mauricio (2015)
The purpose of this research was to determine the influence of the use of social networking sites in the sleep habits of adolescents Vilcabamba School and its relationship to academic performance. This was a qualitative, quantitative study and descriptive. Participated 160 adolescents, to who were applied a survey on the use of social networking sites, sleep habits, subjects approved or disapproved the previous school year and Sleepiness Scale Epworth. The results indicate that the most used social network is Facebook 81.25%; the time slot most used in the evening 60.63%, the average use of social networking is 2.4 hours a day and frequency of use per week the 49.37% of teens use them daily. In the sleep habits on weekdays the hour get up half to 05H51, the average bedtime at 23H00 hours, average sleep latency of 39.28 minutes, and the average daily sleep 7.01 hours. In the application of the Sleepiness Scale Epworth, 35% of teenagers got a mild daytime sleepiness; 33.75% moderate and high daytime sleepiness 31.25%. In the academic performance 54.38% of students passed all their subjects in first opportunity; and 45.64% flunked. It was concluded that teenagers who spent more hours to use social networks, they have daytime more sleepiness than those who do not. Likewise students with higher daytime sleepiness, which get up tired and spend less time sleeping disapprove the largest number of subjects and have poorer academic performance. Keywords: social networking sites, sleep habits, academic performance, adolescents.